The Equity Premium Puzzle, Ambiguity Aversion, and Institutional Quality - Mirakhor, Abbas (IMF Working Papers; Working Paper ;, 2007)
With cross-section data from 53 emerging and mature markets, we provide evidence that equity premium puzzle is a global phenomenon. In addition to risk aversion, equity premium may reflect ambiguity aversion. We explore the sources of equity premium using some pertinent fundamental independent variables, as well as the World Bank institutional quality indexes and other proxies for the degree of ambiguity in the sample countries. Some World Bank and other indexes are statistically significant, which indicates that a large part of equity premium may reflect investor aversion to ambiguities resulting from institutional weaknesses.